2007 Annual Report - Conference on Electrical Insulation and Dielectric Phenomena 2007
DOI: 10.1109/ceidp.2007.4451554
|View full text |Cite
|
Sign up to set email alerts
|

Space charge in LLDPE loaded with nanoparticles

Abstract: Fillers are widely used in insulation systems to achieve specific electrical, mechanical and thermal properties. Recently, polymer nanocomposites have attracted significant attention as a means of improving their performance and widening their utility. To better use the nanocomposites, a thorough understanding of interaction between nanoparticles and their matrix is important. The interaction can be studied by various methods. In the present study we focus our attention on space charge dynamics of linear low d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Increased charge mobility. In our previous paper [22], it was reported that the addition of nano alumina to LLDPE has three consequences. They are (i) enhancement of charge injection, (ii) ionisation possibly due to impurities of nanofillers and (iii) modification of charge trapping characteristics, leading to an increase in charge mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Increased charge mobility. In our previous paper [22], it was reported that the addition of nano alumina to LLDPE has three consequences. They are (i) enhancement of charge injection, (ii) ionisation possibly due to impurities of nanofillers and (iii) modification of charge trapping characteristics, leading to an increase in charge mobility.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of a nanofiller to a polymer matrix has been shown to be a flexible means of tailoring the dielectric properties of materials [1][2][3] and Chen et al [19], for example, have emphasized the unsatisfactory nature of our understanding of charge transport mechanisms. In conventional polymeric insulation, charge transport mechanisms are extremely complicated, when compared with many conducting and semiconducting materials [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Although two decades have passed since the nanodielectric concept was first introduced [17], many aspects of these materials are still poorly understood; Cao et al [18] and Chen et al [19], for example, have emphasized the unsatisfactory nature of our understanding of charge transport mechanisms. In conventional polymeric insulation, charge transport mechanisms are extremely complicated, when compared with many conducting and semiconducting materials [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…From the charge profiles, it is clear that the space charge density increases with the increasing dc voltage. It is worth to note that the development of homo-charge is commonly associated with charge injection processes from the electrodes; that is, positive charge injection at the cathode and negative charge injection at the anode [6].…”
Section: Accumulation Of Space Chargementioning
confidence: 99%